EFFECTIVENESS OF TAX INCENTIVES IN PROMOTING SME DEVELOPMENT IN GOMBE STATE: A CONCEPTUAL REVIEW - Hashidu, Adamu Danazumi; Ogboji, Ogboji Abraham; Onwe, Ogbu Moses (Kashere Journal of Management Sciences, 2025)
Small and Medium Enterprises (SMEs) are widely recognized as critical drivers of economic growth, employment, and innovation, particularly in developing economies like Nigeria. In response to their strategic importance, various tax incentives have been introduced to stimulate SME development. This paper conceptually reviews the effectiveness of tax incentives in promoting SME growth in Gombe State, Nigeria. Drawing on relevant theoretical frameworks (namely, the Tax Incentive Theory, Compliance Cost Theory, and Resource-Based View) alongside recent empirical and policy literature, the study explores the awareness, accessibility, and impact of tax incentives on SME performance. The review reveals that despite the existence of favorable tax policies, their effectiveness in Gombe State remains limited due to low awareness, high informality, institutional weaknesses, and poor policy localization. The study concludes that a more context-specific, inclusive, and transparent implementation of tax incentives is essential to enhance their developmental impact in the state. Key recommendations include simplification of tax processes, localized awareness campaigns, institutional reforms, and coordinated efforts between government agencies. The paper further suggests empirical research to assess tax incentive uptake and their direct impact on SME performance in Northern Nigeria.